Synchronous double primary lung cancer: a report of three cases - Liu, Xue-Dong (AME Publishing Company, 2014)
The incidence of synchronous multiple primary lung cancers is on the rise due to improvements in computed tomography (CT) scanning and increasing use of positron emission tomography scanning and other diagnostic modalities. We report three cases of synchronous double primary lung cancer (DPLC) diagnosed based on CT findings, results of bronchoscopy and histological study. All patients had a long-term history of heavy smoking. Squamous cell carcinoma and small cell carcinoma were the most common histological types in these cases. DPLC frequently involves the upper lobes of left or right lung. Future molecular biological studies on DPLC should be warranted to shed light on the mechanisms underlying the pathogenesis of DPLC and the role of targeted therapy in this condition.